Efficiency of pomalidomide therapy in patients with multiple myeloma refractory to lenalidomide - I. G. Rekhtina; L. P. Mendeleeva (Онкогематология, 2019)
Currently, there has been a marked increase in the number of opportunities for relapsed and refractory multiple myeloma treatment due to emergence of new target drugs. These include pomalidomide, a 3 rd generation immunomodulator capable of treating double refractory multiple myeloma (to lenalidomide and bortezomib). Efficacy and safety of pomalidomide combined with low doses of dexamethasone have been established in MM-003 and STRATUS trials. The summary presents the data on opportunities to further enhance the efficacy of pomalidomide combined with other antitumor drugs in patients with relapsed and refractory multiple myeloma who previously received 4–5 lines of therapy. It has been shown that triplets based on pomalidomide and dexamethasone combined with cyclophosphamide, bendamustine, daratumumab, carfilzomib, elotuzumab are highly effective in double refractory multiple myeloma patients. A combination of pomalidomide with proteasome inhibitors is a promising treatment provided that there is no refractoriness to bortezomib.